2020
DOI: 10.3390/toxics8040087
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Assessment of Exposure Variations on Observed Bioactivity in Zebrafish Chemical Screening

Abstract: The embryonic zebrafish is a powerful tool for high-throughput screening of chemicals. While this model has significant potential for use in safety assessments and chemical prioritization, a lack of exposure protocol harmonized across laboratories has limited full model adoption. To assess the potential that exposure protocols alter chemical bioactivity, we screened a set of eight chemicals and one 2D nanomaterial across four different regimens: (1) the current Tanguay laboratory’s standard protocol of dechori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…Multiple studies suggest BHT is toxic, with a 96-h LC50 ranging from ~20–60 µM and larval behavior being affected at as low as 1 µM [ 57 , 61 ]; however, a separate study did not find significant lethality up to 200 µM, though physical malformations were observed below 100 µM [ 58 ]. The inconsistency between our findings and those of previous studies may be attributed to variable exposure conditions, including chorion status and exposure in pools versus individual wells, both of which can affect the actual internal dose of a chemical [ 62 , 63 , 64 ]. Additionally, while the developmental zebrafish model is highly sensitive to detecting bioactive chemicals, whole-animal bioactivity screening does not provide mechanistic information about a chemical.…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple studies suggest BHT is toxic, with a 96-h LC50 ranging from ~20–60 µM and larval behavior being affected at as low as 1 µM [ 57 , 61 ]; however, a separate study did not find significant lethality up to 200 µM, though physical malformations were observed below 100 µM [ 58 ]. The inconsistency between our findings and those of previous studies may be attributed to variable exposure conditions, including chorion status and exposure in pools versus individual wells, both of which can affect the actual internal dose of a chemical [ 62 , 63 , 64 ]. Additionally, while the developmental zebrafish model is highly sensitive to detecting bioactive chemicals, whole-animal bioactivity screening does not provide mechanistic information about a chemical.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, zebrafish dechorionated embryos (CompTox ZF; [ 18 ]) are more sensitive to chemicals exposure in comparison to chorionated embryos. The presence [ 51 , 52 , 53 ] or absence [ 18 , 21 , 54 , 55 ] of the chorion is important because it acts as a moderator of chemicals’ contact to embryos and their biological response. Chorion removal increases embryos sensitivity, which is an important trait for chemicals hazard identification using this assay [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences relate to initial exposure time (6–24 hpf), the length of exposure time (48–120 h), chorionated versus dechorionated embryos, and static exposure versus media replacement at multiple time points during the test. A recent study compared some of these different protocols and found that they can and do have an effect on the concentration response pattern of the chemicals tested [ 24 ]. However, since the phenotypes produced by the chemicals were similar regardless of the exposure paradigm, the study concluded that the concentration response differences did not affect the conclusions made regarding the bioactivity and potential toxicity of the chemicals tested.…”
Section: Discussionmentioning
confidence: 99%